2021
DOI: 10.1182/bloodadvances.2020003081
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of a phase 2 trial combining lenalidomide with CHOP in angioimmunoblastic T-cell lymphoma

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a frequent T-cell lymphoma in the elderly population that has a poor prognosis when treated with cyclophosphamide, doxorubicin, vincristine, and prednisone  (CHOP) therapy. Lenalidomide, which has been safely combined with CHOP to treat B-cell lymphoma, has shown efficacy as a single agent in AITL treatment. We performed a multicentric phase 2 trial combining 25 mg lenalidomide daily for 14 days per cycle with 8 cycles of CHOP21 in previously untreated AITL patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 47 publications
2
33
1
Order By: Relevance
“…In addition to the RHOA mutation, IDH2 mutations were frequent in these nodal lymphomas of TFH origin, which is consistent with a recent study that reported frequent mutations of IDH2 affecting residue R172 in patients with AITL (Fig. 2A) [25]. We also found that TP53 mutations occurred commonly in PTCL-NOS, similar to the results of previous studies reporting the role of genetic alterations including TP53 in these tumors [26].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the RHOA mutation, IDH2 mutations were frequent in these nodal lymphomas of TFH origin, which is consistent with a recent study that reported frequent mutations of IDH2 affecting residue R172 in patients with AITL (Fig. 2A) [25]. We also found that TP53 mutations occurred commonly in PTCL-NOS, similar to the results of previous studies reporting the role of genetic alterations including TP53 in these tumors [26].…”
Section: Discussionsupporting
confidence: 92%
“…A phase II study of 40 patients with newly diagnosed PTCL receiving lenalidomide + CHOEP resulted in an ORR of 69% with a CR of 48%; however, AEs (mainly hematological) led to a high discontinuation rate [64]. A similar study combining lenalidomide with CHOP specifically in elderly patients with AITL yielded similar results and did not reach the primary endpoint [65]. In response, induction chemotherapy has been replaced by other novel agents, notably in a recently reported phase II study investigating the combination of induction lenalidomide with romidepsin for elderly patients who are not candidates for intensive chemotherapy.…”
Section: Lenalidomidementioning
confidence: 98%
“…An integrative analysis of this trial has been recently published, lenalidomide was given in association with CHOP every 21 d for eight total cycles[ 65 ]. CHOP was administered on day 1, and lenalidomide was added at a daily dose of 25 mg for 14 d every 21 d. Out of 78 patients included in the efficacy analysis, ORR was 56%, with a CR rate of 41%.…”
Section: New Perspectivesmentioning
confidence: 99%
“…CHOP was administered on day 1, and lenalidomide was added at a daily dose of 25 mg for 14 d every 21 d. Out of 78 patients included in the efficacy analysis, ORR was 56%, with a CR rate of 41%. The median dose intensity for lenalidomide was 81%, and 55% of total cases completed the study; the most common reasons for early treatment discontinuation were PD and toxicity[ 65 ]. After a median follow-up of 45 mo, 2-year PFS and OS were 42.1% and 59.2%, respectively; the presence of DNMT3A mutation appeared related with shorter PFS.…”
Section: New Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation